Специфіка класифікації релігійно-паломницьких турів - Патійчук, Віктор; Patiychuk, Victor (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Узагальнено суть понять «релігійно-паломницький туризм»і «паломництво» й визначено співвідношення між цими науковими категоріями. Розглянуто методичні особливості проведення класифікації релігійно-паломницьких турів та вказано на специфіку таксономії основних видів і форм релігійного паломництва. Розкрито основні функції релігійно-паломницького туризму. Проаналізовано різноманітні наукові підходи до класифікації релігійнопаломницьких турів. Запропоновано авторську схему й принципи класифікації релігійного паломництва. Обобщается суть понятий «религиозно-паломнический туризм» и «паломничество» и определяется соотношение между этими научными категориями. Рассмотрены методические особенности проведения классификации религиознопаломнических туров и указана специфика таксономии основных видов и форм религиозного паломничества. Раскрыты основные функции религиозно-паломнического туризма. Проанализированы различные научные подходы к классификации религиозно-паломнических туров. Предложены авторская схема и принципы классификации религиозного паломничества. The essence of the concepts of «religious and pilgrimage tourism» and «pilgrimage» is overviewed and the relationship between these research categories is defined. There are methodical features of classification of religious pilgrimage tours in the article and the specificity of taxonomy of main types and forms of religious pilgrimage is given. The basic functions of religious and pilgrimage tourism are revealed. The variety of scientific approaches to classification of religious pilgrimage tours is analyzed. The author offered his own scheme and principles of religious pilgrimage classification.
The Specificity of Classification of Religious Pilgrimage Tours
Keywords: релігійно-паломницький туризм; паломник; класифікація; функції паломництва; релігійно-паломницький тур; religious and pilgrimage tourism; pilgrim; classification; functions of pilgrimage; religious pilgrimage tour